Analytical Calculations of Some Effects of Tidal Forces on Plants on the International Space Station - Henri Gouin (MDPI AG, 2021)
Among the phenomena attributable to the Moon’s actions on living organisms, one of them seems to be related to analytical fluid mechanics: along the route of the International Space Station around the Earth, experiments on plants have revealed leaf oscillations. A parametric resonance due to a short period of microgravitational forces could explain these oscillations. Indeed, Rayleigh-Taylor’s instabilities occurring at the interfaces between liquid-water and its vapor verify a second-order Mathieu differential equation. This is the case of interfaces existing in the xylem channels of plant stems filled with sap and air-vapor. The magnitude of the instabilities depends on the distances between the Moon, the Sun, and the Earth. They are analogous, but less spectacular, to those that occur during ocean tides.